(untitled) (Research, Society and Development, 2024)
Uterine torsion (UT) constitutes an obstetric emergency that predominantly impacts advanced pregnancies and, although rare, accounts for 5 to 10% of all mare-related obstetric emergencies. The condition is characterized by a rotation of the uterine body along the longitudinal axis, which may affect the uterine horns, and its etiopathogenesis remains undefined. The degree of torsion can range from 180 to 720 degrees and is positively correlated with reserved prognosis. This article aims to report the case of a mare in late pregnancy diagnosed with uterine torsion. A 13-year-old Criollo mare in late pregnancy presented to Hospital de Clínicas Veterinárias – UFRGS with a 5-day history of abdominal discomfort. Rectal palpation, ultrasonography, and gynecological examination revealed the presence of uterine torsion. A flank laparotomy was performed during which the manual repositioning of the uterus into its anatomical position was unsuccessful, leading to the decision to euthanize the animal. The body was submitted for necropsy at Serviço de Patologia Veterinária – UFRGS. A 360-degree counterclockwise torsion of the right uterine horn through the broad uterine ligament and around the left uterine horn was observed, as well as a 360-degree torsion of the uterine body around its axis in the same direction. The fetus was already in advanced autolysis. Histologically, endometrial necrosis was present, along with pronounced hemorrhage, fibrin deposition, and inflammatory infiltrate in the uterus. The severe uterine torsion, elevated heart rate, advanced pregnancy and delayed hospital referral were the main factors responsible for the worse prognosis, leading to mare and fetal death.